Tapia Syndrome as a Postoperative Complication of LMA Use During TFCC Reconstruction: A Rare Case Report - Conni Nabilla Nur Shabrina; Yanti Nurrhokmawati; Fansuri Ikhsan; Realita Malik (International Medical Journal Corp. Ltd, 2025)
Background: Tapia Syndrome is a rare neurological condition characterized by concurrent paralysis of the hypoglossal nerve (XII) and the laryngeal branch of the vagus nerve (X), typically resulting from mechanical trauma or excessive pressure to the neck area during general anesthesia. It typically presents with symptoms such as dysarthria, dysphagia, and ipsilateral tongue deviation. One reported risk factor is the use of airway devices such as the Laryngeal Mask Airway (LMA), which can exert localized pressure on these cranial nerves. Although uncommon, this complication is important to recognize, particularly among anesthesiologists and otolaryngologists, due to its impact on speech and swallowing functions. Objective : To report a case and management of a patient with Tapia Syndrome Methods: The study employs a case report methodology supported by a literature review through Pubmed, Cochrane Library, and NCBI using the keywords tapia syndrome, paralysis of nervus XII and IX. 15 articles were found, and articles were selected based on inclusion and exclusion criteria, and 11 relevant studies were obtained. Results: The patient presented with dysarthria and tongue deviation on the first postoperative day, with no signs of central neurological deficits. A clinical diagnosis of Tapia Syndrome was made based on the symptoms and aesthesia history. Supportive therapy and speech rehabilitation were initiated, resulting in gradual recovery over several weeks. Literature review suggests that most similar cases show good outcomes with conservative management. Conclusion: Tapia Syndrome is a rare but significant complication of LMA use during general anesthesia. Awareness of potential cranial nerve injury during airway device placement is essential, particularly in surgeries involving head and neck positioning. Early diagnosis and multidisciplinary management were critical in the patient’s recovery